Determinação de Si e Y em amostras agronômicas por espectrometria de emissão óptica com plasma induzido por micro-ondas - Dias, Ellen Aguilar (Universidade Federal de São Carlos, 2021)
Different demands for analytical responses are presented in agricultural research. In this approach, this dissertation, divided into two chapters, seeks to offer analytical alternatives for plant breeding and fish nutrition projects. In the first chapter, a procedure was developed to determine silicon in plant samples, specifically sorghum (Sorghum bicolor), used in animal feed and bioenergy production. The presence of high levels of Si in the plant can cause damage to boilers used for the generation of bioenergy. As an alternative to the use of HF, usually employed in the digestion of samples for the determination of Si, the use of HBF4 acid and its possible products of reaction were evaluated. Microwave-assisted digestion was used for sample preparation and determination by microwave-induced plasma optical emission spectrometry (MIP OES). Different volumes of HBF4 acid (0.2 mL, 0.5 mL, 1.0 mL and 2.0 mL) were studied, indicating the most appropriate 0.2 mL volume, with 99% recovery in samples previously analyzed by X-ray fluorescence spectrometry (XRF), and 0.03 g kg-1 limit of detection. The digestion with HBF4 showed that about 70% of Si solubilized was found as fluorosilicic acid. Also, the equilibrium conditions of the reactions involved indicated the formation of HF, confirming the need to employ strategies to avoid damage to the components of the equipment. The mass fractions of Si found in the analyzed sorghum samples ranged from 0.67 to 4.57 g kg-1. The second chapter presents the development and validation of a sample preparation procedure for the quantification of Y by MIP OES. It was used as a marker to evaluate digestibility in ingredients, diets, and fish faeces. The developed procedure presented adequate linearity. It was assessed by values of r and r2, evaluated residues, and homoscedasticity. Selectivity was evaluated in the study related to matrix effects, obtaining satifastor results. Precision, which included repeatability and intermediate precision, presented cv < 0.5%. The limits of detection and quantification obtained were 0.60 mg kg-1 and 1.99 mg kg-1, respectively.
Determination of Si and Y in agronomic samples by microwaves induced plasma emission spectrometry
Keywords: Silício; Ítrio; MIP OES; Ácido fluorbórico; Validação do método; Silicon; Yttrium; Tetrafluoroboric acid; Method validation; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE